Enhancement of luminous efficacy for light-emitting diodes lamps by adding CaSr2(PO4)2:Eu3+ phosphor - Ho Minh Trung; My Hanh Nguyen Thi (Institute of Advanced Engineering and Science, 2023)
Through employing the fluid ignition technique, we created the samples CaSr2(PO4)2:Eu3+ with Eu3+ incorporated then assessed them in the form of contactless optical heat measurement as well as solid-state illumination. We identified the attributes for these samples including X-ray diffraction (XRD), photoluminescent spectroscopy, Fourier transmute infrared spectroscopy (FTIS) along with photoluminescent spectroscopy correlating with temperature. XRD, along with FTIS, validates that the one-stage samples were formed via the orthophosphate anion (PO4)3- . In the case of these samples, nUV recreation under 395 nm generated potent, orange-red discharge lines under 592 nm as well as 615 nm, which is consistent with the standard shifts between 5D0 and 7F1 as well as 5D0 and 7F2 for the Eu3+ ions. The International Commission on Illumination (CIE) coordinates (0.65, 0.35) based on the hue scale validate the red discharge. For the task of attaining optical heat measurement, we took advantage of the fluorescent intenseness proportion technique that utilizes heat-incorporated discharge states of 5D1 as well as 5D0 for Eu3+ . The samples have maximum responsiveness reaching roughly 0.0023 K-1 under 323 K or small heat levels. According to the outcomes, it is possible to utilize the samples when it comes to contactless optical heat measurement as well as solid-state illumination.